Replacement of osmotic minipumps to extend the intracerebral infusion time of compounds into the mouse brain - Stefan A. Grathwohl; Mathias Jucker (BioTechniques)
Osmotic minipumps represent a convenient and established method for targeted delivery of agents into the brain of small rodents. Agents unable to cross the blood brain barrier can be directly infused into the brain parenchyma or lateral ventricle through implanted cannulas. The small volume of the minipump reservoir typically limits the infusion time to 4–6 weeks. Pump changes with reattachment of a new pump reservoir to the cannula might lead to brain tissue irritation or increased intracranial pressure associated with hydrocephalus. Here, we describe a pump reservoir exchange technique using a Y-shaped connection piece (Y-con) between the infusion cannula and the pump reservoir. This allows repeated replacement of a subcutaneously installed pump reservoir for brain delivery of agents in mice. Experimental evaluation of Y-con pump replacement revealed no signs of tissue irritation or hydrocephalus and allowed extended controlled delivery of infusion agents in the brain.